2015
DOI: 10.24310/espsiescpsi.v8i3.13243
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de afrontamiento en adultos mayores en función de variables sociodemográficas

Abstract: Para conseguir la adaptación a los cambios que se producen en el envejecimiento se ponen en marcha una serie de estrategias de afrontamiento. En este estudio, 275 adultos mayores, que acuden a un centro de mayores a realizar actividades, respondieron a una serie de datos sociodemográficos y al Cuestionario de Afrontamiento del Estrés (CAE) mediante una entrevista semiestructurada. El objetivo es analizar el uso de las estrategias de afrontamiento en función de diversas variables sociodemográficas, mediante el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This questionnaire has been developed and validated in Spain, and from exploratory and confirmatory studies, it has shown an adequate factorial structure, identifying reliability with Cronbach’s alpha of 0.75. 20 , 21 It is made up of 42 items divided into seven subscales: Search for Social Support (SSS), Open emotional expression of aggressiveness and irritability (OEE), Religion (RLG), Focus on solving the problem (FSP), Avoidance (AA), Negative Self-Focusing (NSF) and Positive Reappraisal (PR). The cut-off points for the CAE questionnaire scores were: inadequate coping with stress.…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaire has been developed and validated in Spain, and from exploratory and confirmatory studies, it has shown an adequate factorial structure, identifying reliability with Cronbach’s alpha of 0.75. 20 , 21 It is made up of 42 items divided into seven subscales: Search for Social Support (SSS), Open emotional expression of aggressiveness and irritability (OEE), Religion (RLG), Focus on solving the problem (FSP), Avoidance (AA), Negative Self-Focusing (NSF) and Positive Reappraisal (PR). The cut-off points for the CAE questionnaire scores were: inadequate coping with stress.…”
Section: Methodsmentioning
confidence: 99%